ADVANCEMENTS IN EEG TECHNOLOGY AND AI INTEGRATION IN NEUROLOGY - Djurayeva Nigora Rakhbarovna; Ziyovuddinova Samira Jaloliddinovna; Kholmetov Shovkat Sherimatovich; Zuparov Ilkhom Bakhodirovich (Western European Studies, 2025)
this article discussesthe role of electroencephalography in the diagnosis of pathologies and diseases of the brain
Keywords: Artificial intelligence; membrane potential; resting potential